2019
DOI: 10.1063/1.5081108
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic quantum transition-state theory in the golden-rule limit. I. Theory and application to model systems

Abstract: We propose a new quantum transition-state theory for calculating Fermi's golden-rule rates in complex multidimensional systems. This method is able to account for the nuclear quantum effects of delocalization, zero-point energy and tunnelling in an electron-transfer reaction. It is related to instanton theory but can be computed by path-integral sampling and is thus applicable to treat molecular reactions in solution. A constraint functional based on energy conservation is introduced which ensures that the dom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(85 citation statements)
references
References 132 publications
(195 reference statements)
1
84
0
Order By: Relevance
“…In contrast, as we have shown in Ref. 40, GR-QTST always reduces to the correct classical expression (Eqn. (9)) in the high-temperature limit where the ring polymer collapses.…”
Section: Methodsmentioning
confidence: 54%
See 3 more Smart Citations
“…In contrast, as we have shown in Ref. 40, GR-QTST always reduces to the correct classical expression (Eqn. (9)) in the high-temperature limit where the ring polymer collapses.…”
Section: Methodsmentioning
confidence: 54%
“…However, we could show the unsuitability of this assumption by comparing Wolynes theory 32 and our newly developed GR-QTST. 40,41 In an earlier study it was observed that GR-QTST and Wolynes theory predict the same rate for a spin-boson model in the quantum limit. 40 In contrast to this, the two theories predict quantum correction factors that differ by a factor of 6 for the atomistic system, therefore making it impossible to argue that a spin-boson model is a good approximation in this case.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nonetheless, a good understanding of the instanton paths has helped in the development of a number of methods based on path-integral sampling which are applicable to reactions in solution. 61,62,104 We hope that the information obtained on the instanton in this work will help derive novel path-integral-based rate theories which can describe the inverted regime more rigorously.…”
Section: Discussionmentioning
confidence: 94%